Novel Double Cantilever Beam experiments and related evaluation methods to investigate the fracture behaviour of adhesive layers in modes I and III - Schrader, Peer; Justus Liebig University Giessen (My University, 2022)
This cumulative dissertation consists of four manuscripts dealing with the fracture mechanics testing of adhesive layers in pure loading modes I and III. Different Double Cantilever Beam (DCB) test specimens are used to investigate the energy release rate and cohesive traction of rigid, epoxy-based and soft, rubber-based adhesive systems under different boundary conditions. New test setups and evaluation methods are developed to gain a better understanding of the fracture behaviour of these adhesive joints and to investigate the influence of different evaluation methods on the results. In order to investigate the fracture behaviour of epoxy-based bonded joints, the Out-of-plane Loaded Double Cantilever Beam (ODCB) test was extended to higher loading rates, which, with the help of a local strain measurement, allowed the determination of fracture energy and cohesive traction in mode III at increased loading rates for the first time. However, it became apparent that ODCB tests, which have to be carried out in a bi-axial testing machine, are probably not suitable for testing under impact. Hence, uni-axial test rigs were developed to enable mode III testing of such adhesive joints. These were carried out quasi-statically to investigate the influence of different evaluation methods in more detail. The rate-dependent fracture behaviour of soft, rubber-like adhesives was also investigated, which includes both a creep load in pure mode I and an investigation at increased loading rates in modes I and III. For the investigation under creep loading, a method is proposed which allows the control of the tests on constant J-integral. In addition, the influence of the material behaviour within the process zone is examined in more detail, as this influences both the creep behaviour and the cohesive stresses and their evaluation methods. For the determination of the cohesive traction, a new method is developed within the scope of the work, which is based on the strain measurement along with the adherends and thereby enables a determination of the dependence of the cohesive stresses on the loading rate along the entire adhesive layer. A comparison with the conventional method of determining the cohesive traction from the derivative of the energy release rate with respect to the crack opening displacement showed that the currently applied method may deliver inadequate results. The results of this work thus extend the state of the state of research and in doing so demonstrate new methods that can be used in DCB tests in modes I and III to provide new insights into the fracture behaviour of adhesively bonded joints.
Keywords: J-Integral; fracture mechanics; Double Cantilever Beam; Out-of-plane loaded Double Cantilever Beam; cohesive traction; Irwin-Kies-Equation; Energy Release Rate; process zone; rubber-like adhesives; epoxy adhesives; backface strain; rate-dependency; adhesive joints; adhesive testing; ddc:620